(untitled) (Veterinary Science, 2017)
The aim of the present report is to bring up to date knowledge about fractures in long bones of immature dogs. The etiology, types of fractures and appropriate treatments will be analyzed. Fractures in the appendicular skeleton are closely related to bone type and patient. The ideal repair method in immature animals should net compromise growth and bone biomechanics, allowing support and limbs use during the treatment period